2018
DOI: 10.1001/jamanetworkopen.2018.6054
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Simulated Institutional Gender Equity Initiative With Gender-Based Disparities in Medical School Faculty Salaries and Promotions

Abstract: Key Points Question What is the true magnitude of differences in salary, time to promotion, and accumulated wealth between male and female faculty, and how are these measures associated with a set of institutional gender equity initiatives? Findings In this quality improvement simulation study of salaries of 1481 faculty, the salary gap and time to promotion decreased after implementation of gender equity initiatives; however, small persistent differences w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…[7][8][9][10][11][12][13] This effect is seen in clinical, 14 research 15 and aca demic 16,17 environments. Inequities start at the early stages of a medical career, 18,19 deepen with time, 20 continue into retire ment 21 and affect lifetime wealth, 22 with estimates as high as $2.5 million over a 30year career. 23 The pay gap in medicine per sists after adjustment for factors like physician age, specialty, number of hours worked and practice characteristics.…”
Section: Is the Gender Pay Gap Real?mentioning
confidence: 99%
“…[7][8][9][10][11][12][13] This effect is seen in clinical, 14 research 15 and aca demic 16,17 environments. Inequities start at the early stages of a medical career, 18,19 deepen with time, 20 continue into retire ment 21 and affect lifetime wealth, 22 with estimates as high as $2.5 million over a 30year career. 23 The pay gap in medicine per sists after adjustment for factors like physician age, specialty, number of hours worked and practice characteristics.…”
Section: Is the Gender Pay Gap Real?mentioning
confidence: 99%
“…This persistent difference is especially notable when compounded over a career. For example, recent simulations of gender pay gaps in medical sciences suggest that a pay gap of just 3% can accumulate into a difference of over $500,000 in additional accumulated wealth across a scientist's career (Rao et al, 2018).…”
Section: Compensationmentioning
confidence: 99%
“…We look at 5 articles published in 2018 and 2019 in JAMA Network Open [1][2][3][4][5] (Box) that examine disparities in different subsets of medicine or in areas related to careers in academic medicine, disparities that not only limit women's career trajectories but also have a significant impact on their compensation and subsequently their retirement security. As Weng et al noted, 1 inequity in a single context may set a precedent for inequity in others, which then contribute to greater disparity.…”
mentioning
confidence: 99%
“…(Women hold 25% of full professor positions and 37% of associate professor positions in the United States. 7 ) Rao et al 4 noted that, to account for lower additional accumulated wealth and longer life expectancy, a woman would have to spend $0.60 for every $1 spent by a male counterpart for her resources to last through retirement. The authors found that the salary gap and time to promotion The words used to describe men vs women differ in significant ways, which can affect their careers.…”
mentioning
confidence: 99%